Chronic Cholangitides: Aetiology, Diagnosis, and Treatment. Issue 5617 (31st August 1968) - Sherlock, Sheila
Abstract : A number of different chronic diseases affect the intrahepatic bile radicles or cholangioles. They include primary and secondary sclerosing cholangitis, primary biliary cirrhosis, chronic cholestatic drug jaundice, atresia, and carcinoma. Aetiological factors include infection, immunological changes, hormones, and congenital defects. Patients with chronic cholestasis have decreased bile salts in the intestinal contents and suffer from a bile salt deficiency syndrome. Failure to absorb dietary fat is managed by a low-fat diet and by medium-chain trigly-cerides which are absorbed in the absence of intestinal bile salts. Fat-soluble vitamin deficiencies are prevented by parenteral vitamins A, D, and K1 . Calcium absorption is defective, and improvement may follow intramuscular vitamin D, medium-chain triglycerides, a low-fat diet, and oral calcium supplements. In partial intestinal bile salt deficiency the anionic bile-salt-chelating resin cholestyramine controls pruritus though steatorrhoea increases. Pruritus associated with total lack of intestinal bile salts is managed by methyl-testosterone or norethandrolone, though the jaundice increases.